2020
DOI: 10.1136/bmjopen-2020-039552
|View full text |Cite
|
Sign up to set email alerts
|

Use of implantable meshes for augmented rotator cuff repair: a systematic review and meta-analysis

Abstract: ObjectiveTo appraise studies reporting on clinical effectiveness and safety of surgical meshes used to augment rotator cuff repairs (RCRs).DesignSystematic review and meta-analysis.Data sourcesMEDLINE, Embase and Cochrane databases were searched between April 2006 and April 2020.Eligibility criteriaAll studies evaluating adults (≥18 years) undergoing RCR were considered. There were no language restrictions.Data extraction and synthesisScreening, data extraction and quality appraisal were conducted by two indep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 87 publications
(86 reference statements)
0
18
0
1
Order By: Relevance
“…In a recent systematic review, Bailey et al 2 reported a lower retear rate and improved American Shoulder and Elbow Surgeons scores in patients treated with RCR when augmented or interposed with graft. Much of the recent interest in augmentation has revolved around the use of xenografts 3 and synthetics, 4 whichdalong with human allograftdhave significant disadvantages including cost and risk of disease transmission. Use of an autograft would be ideal for the setting of cuff deficiency or footprint augmentation to avoid the aforementioned disadvantages while providing the optimal biological and vascular environment for tissue healing.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent systematic review, Bailey et al 2 reported a lower retear rate and improved American Shoulder and Elbow Surgeons scores in patients treated with RCR when augmented or interposed with graft. Much of the recent interest in augmentation has revolved around the use of xenografts 3 and synthetics, 4 whichdalong with human allograftdhave significant disadvantages including cost and risk of disease transmission. Use of an autograft would be ideal for the setting of cuff deficiency or footprint augmentation to avoid the aforementioned disadvantages while providing the optimal biological and vascular environment for tissue healing.…”
Section: Discussionmentioning
confidence: 99%
“…7 Not surprisingly, shoulder surgeons have explored whether augmentation of cuff repair would not only result in better cuff integrity but also reduce retear rates. 5,[8][9][10] An earlier study by Barber et al has been promising reporting intact repairs in 85% compared with 40% in nonaugmented repairs at a mean follow-up of two years. 9 Similarly, Cai et al have shown that graft augmentation with three-dimensional collagen reduced the retear rate to 14% compared with 34% in a control group who underwent arthroscopic repair only.…”
Section: See Related Article On Page 38mentioning
confidence: 98%
“…A recent meta-analysis has concluded that the current evidence is not robust. 10 Although small improvements in pain and patient-reported outcome measures and a moderate reduction in retear rates for both synthetic and human allograft patches were observed, study bias and heterogeneity strongly suggested that the results should be interpreted with extreme caution. 10 So maybe autograft, such as the long head biceps tendon, is a better option in these cases?…”
Section: See Related Article On Page 38mentioning
confidence: 99%
See 1 more Smart Citation
“…Especially for patients with small to medium tears, significant improvements can be found after physical therapy and surgical treatments (Schmidt et al, 2015). Many clinicians contribute a lot to explore the PROs of surgical treatment for rotator cuff tears and many patients have good outcome postoperatively (Baldwin et al, 2020;Oh et al, 2020;Tashjian et al, 2020). The effect of surgical repair of the rotator cuff tendon is not always satisfactory.…”
Section: Surgeries For Rotator Cuff Repairmentioning
confidence: 99%